2010
DOI: 10.1021/jp908850j
|View full text |Cite
|
Sign up to set email alerts
|

Transport, Analyte Detection, and Opto-Electronic Response of p-Type CuO Nanowires

Abstract: In this article, we introduce and provide details on a large-scale, cost-effective pathway to fabricating ultrahigh dense CuO nanowire arrays by thermal oxidation of Cu substrates in oxygen ambient. The CuO nanowires that are produced at ∼500 °C for ∼150 min feature an average length and diameter of ∼15 µm and ∼200 nm, respectively. The room temperature device-related characteristics such as transport, analyte detection and opto-electronic response of individual CuO nanowires have been probed by fabricating si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 34 publications
3
131
0
1
Order By: Relevance
“…Lower temperatures lead to high resistance values that made difficult the gas tests. The sensing mechanism of NH 3 by CuO was explored in the past [15,25]. To that end, the classic conduction model [26] of metal-oxides was adopted; surface oxygen species withdraw electrons from CuO decreasing the resistance due to the generation of holes in the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower temperatures lead to high resistance values that made difficult the gas tests. The sensing mechanism of NH 3 by CuO was explored in the past [15,25]. To that end, the classic conduction model [26] of metal-oxides was adopted; surface oxygen species withdraw electrons from CuO decreasing the resistance due to the generation of holes in the material.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different techniques to synthesize CuO nanowires, such as electro-spinning [17] and template-assisted growth [11], the direct oxidation of Cu foils [14][15][16] is easy to implement and scalable, providing pleasing results in terms of crystallinity and material quality [14]. These facts are triggering the research on one-dimensional (1D) CuO nanostructures [5,12,13,15,16], but the scope of their sensing characteristics remains uncompleted according to the authors' best knowledge since the studies performed with individual CuO nanowires have been limited up to now [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in this study is on CuO, a p-type semiconducting material, which has been reported for detection of NO x [9][10][11][12][13][14], CO [12,[15][16][17], H 2 [18][19][20], and ethanol [14,[20][21][22][23][24][25]. CuO has also been studied as a NO x reduction catalyst in SCR [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Although CuO has received wide attention since the discovery of high temperature cuprate superconductors, its electronic structure has not been fully settled. The onset of direct-allowed absorption has been determined at 1.57 eV at low temperature [15], but the type of band gap (direct [28][29][30] or indirect [12,16,21,31]) remains controversial. The correlated nature of CuO presents a greater challenge for electronic structure calculations.…”
mentioning
confidence: 99%